Epidemiology and Outcome of Burn Patients in the Burns Specialty Center at Al-Diwaniyah Province, Iraq, 2019 (Medico Legal Update, 2020)
Background: The stressful consequences of burns included physical injury, psychological trauma andfinancial problem not only for the victim himself but also to his family. Burn victims may pass through painfulexperience until getting improved or unfortunately die from a number of burn associated complications; inaddition some of them remain crippled for the rest of their lives. Variations among sociodemographic andcultural characteristics of different nations have variable effects of the outcome of burn injuries.Aim of the Study: The current study was carried out in order to identify demographic characteristics ofburn patients in association with outcome of burn injuries in terms of morbidity and mortality during theyear 2019.Patients and Method: Burns Specialty Center lies in Al-Diwaniyah province, mid-Euphrates region of Iraq.This region is located southern to Baghdad. It is an agricultural Province with a population of approximately1.5 million. The Burn center is a referral point for burn victims from this region as well as from other midEuphrates regions such as Najaf, Babel, Nasiriyah and Simawa. The total number of burn patients admittedto the center during the year 2019 was 411Results: The present study revealed that the age group 7 to 30 was the most frequently affected groupaccounting for 42.3 %. With respect to gender, children in the current study showed comparable male andfemale distribution, but, patients above 6 years of age were more likely to be female than to be male;however, statistical wise the difference was not significant. With respect to circumstances, in the currentstudy home accidents were the most frequent situation of burn injury in which patients were mostly childrenor adult females. In the current study, the most frequent agent was flame, followed by scald, then electricaland chemical injuries. Mortality rate in the current study was 13.6 %.Conclusion: domestic injuries dominated the circumstances of burn, adult patients were most likely women,flame and oil were the most commonly encountered agents and occupational injuries were mainly seen inadult males.